The equilibrium relationship between public and total employment. The importance of endogenous non-labour income - Erling Holmøy (Statistics Norway, Research Department, 2014)
This paper analyses the general equilibrium relationship between increases in tax financed public employment and total employment, emphasizing one income effect: Reallocating employment from the private to the public sector reduces non-labour income in the form of profits distributed to workers, since there are no profits in public sectors. This may cause a positive general equilibrium relationship between total employment and tax financed public employment, even if the uncompensated wage elasticity of labour supply is positive. Such a positive relationship is consistent with the stylized facts in generous welfare states such as Norway and Sweden. Precise conditions for a positive general equilibrium relationship are derived within the simplest possible model. It is also shown that if such a positive relationship exists, it will be stronger the higher is public employment. This mechanism turns out to be crucial when explaining the employment effect of an increase in tax financed public employment generated by a realistic CGE model of the Norwegian economy.
Keywords: H20; H31; 330; Taxation; Labour supply; General equilibrium effects